The effectiveness of superplasticizer in concrete - Ho, Sock Hui (School of Environmental Engineering, University Malaysia Perlis, 2016)
This research is conducted to observe the effectiveness of superplasticizer admixture adding in mix concrete in term of workability and properties of concrete. Superplasticizer is a chemical admixture that can reduce high range water and added to concrete mixtures to improve workability. For this research the grade of concrete was designed at 35 MPa. The different dosage of superplasticizer with 0.2 %, 0.3 %, 0.8 % and 1.5 % was used to achieve different degree of workability and also study optimum dosage of admixture used in concrete. This research is conducted in laboratory to investigate the fresh concrete in term of slump test while hardened concrete in term of compressive strength, concrete strain and flexural strength with curing 7, 14 and 28 days. The highest and lowest value of compressive strength were obtained with the addition of 0.3 % and 0.8 % superplasticizer respectively. Whereas the flexural strength of concrete with 0.3 % of superplasticizer achieve 1.41 MPa. Strain of concrete was measured by using strain gages at different point while it show improve in strain with additional 0.2 % of superplasticizer. Therefore, it was found reduced 30 % of water content, the additional superplasticizer exhibits increase in term of strength and strain.